Tinjauan Etika Bisnis Syari’ah Terhadap Praktek Pembayaran Konsinyasi Antara Pihak Komisioner Dengan Pihak Distributor - Hanafi, Yusron (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research examines the practice of Consignment practiced by some traders in the Ngawi large market, by asking the Distributor to send the goods needed by the Merchants. The practice of Consignment in the Ngawi Big Market between the merchants and the Commissioner is largely not in accordance with the rules of the Consignment discipline and the values in the axioms of Sharia Business Ethics. Therefore, this research wants to find out what is the reason why traders and distributors apply the Consignment system in their business activities. This research aims to provide an assessment based on Shari'ah Business Ethics on the behavior of traders and commissioners who apply the consignment system. The research method used is Qualitative with Inductive analysis and Normative approach. The results of the study state that the reason the traders apply the Consignment system is due to limited capital, while the reason the Distributor applies the consignment system is due to difficulties in selling their production goods. According to Shari'ah Business Ethics, the consignment practices carried out by traders in the Ngawi Big Market violate the values in Shari'ah Business Ethics such as Dzolim, fraud, and not keeping promises.